Structural and Functional Consequences Induced by Post-Translational Modifications in α-Defensins. (28th August 2011) - Balducci, Enrico; Bonucci, Alessio; Picchianti, Monica; Pogni, Rebecca; Talluri, Eleonora
Abstract : HNP-1 is an antimicrobial peptide that undergoes proteolytic cleavage to become a mature peptide. This process represents the mechanism commonly used by the cells to obtain a fully active antimicrobial peptide. In addition, it has been recently described that HNP-1 is recognized as substrate by the arginine-specific ADP-ribosyltransferase-1. Arginine-specific mono-ADP-ribosylation is an enzyme-catalyzed post-translational modification in which NAD + serves as donor of the ADP-ribose moiety, which is transferred to the guanidino group of arginines in target proteins. While the arginine carries one positive charge, the ADP-ribose is negatively charged at the phosphate moieties at physiological pH. Therefore, the attachment of one or more ADP-ribose units results in a marked change of cationicity. ADP-ribosylation of HNP-1 drastically reduces its cytotoxic and antibacterial activities. While the chemotactic activity of HNP-1 remains unaltered, its ability to induce interleukin-8 production is enhanced. The arginine 14 of HNP-1 modified by the ADP-ribose is in some cases processed into ornithine, perhaps representing a different modality in the regulation of HNP-1 activities.